Resilience of Farming Labours Based on Bawon System Tradition and Ani-Ani Traditional Appliance In Indigenous Community of Urug Societies In Bogor, West Java - Bahagia - Bahagia; Rimun Wibowo; Fachruddin Majeri Mangunjaya; M.Azar Al-Wahid (Universitas Gadjah Mada, 2020)
The purpose of this research is to investigate bawon system tradition and traditional appliance in the traditional community to empower farming labours toward community resilience. The research method used is an ethnographic qualitative approach. This method is applied because the research is related to cultural, ritual, traditional, and social phenomena. The data are collected through in-depth interview, observation, and documentation. The selection of informants as samples uses purposive sampling technique. The result is probed meticulously through technique triangulation and source triangulation. The result shows that bawon system is a tradition in agriculture to assist landless people for cultivating. It leads to create agriculture worker resilience because the landless people can fulfil their basic needs from this mechanism, and they will not be unemployed amid the implementation of modern agricultural technology. Another result is the use of a traditional tool like ani-ani which can empower women resilience because women will not lose their vanity in farming activity. Besides, it can attain traditional and cultural resilience because ani-ani and bawon system can be categorized as traditional culture.